Differences of apathy perfusion correlates between Alzheimer's disease and frontotemporal dementia. A 99mTc-HMPAO SPECT study with automated Brodmann areas analysis. (1st March 2022) - Valotassiou, Varvara; Sifakis, Nikolaos; Tzavara, Chara; Lykou, Evi; Tsinia, Niki; Kamtsadeli, Vasiliki; Sali, Dimitra; Angelidis, George; Psimadas, Dimitrios; Tsougos, Ioannis; Papageorgiou, Sokratis G.; Georgoulias, Panagiotis; et al.
Abstract: Objectives: To explore differences of apathy perfusion correlates between Alzheimer's disease (AD) and Frontotemporal dementia (FTD) using perfusion SPECT. Methods: We studied 75 FTD and 66 AD patients. We evaluated apathy using Neuropsychiatric Inventory (NPI). We compared perfusion of BAs on left (L) and right (R) hemisphere in AD and FTD. Results: Apathy in AD was significantly and negatively correlated with dorsolateral prefrontal cortex bilaterally, right anterior prefrontal cortex, inferior frontal cortex bilaterally, especially on the right, orbital part of inferior frontal gyrus bilaterally, left dorsal anterior cingulate cortex, right primary and secondary visual cortex, and with bilateral anterior and dorsolateral prefrontal cortex, inferior frontal cortex and orbital part of inferior frontal gyrus, bilaterally, bilateral anterior -ventral and dorsal- cingulate cortex, left posterior ventral cingulate cortex, right inferior, middle and anterior temporal gyri, entorhinal and parahippocampal cortex in FTD. Conclusions: Significant overlapping of apathy perfusion correlates between AD and FTD is seen in frontal areas and anterior cingulate. Right occipital cortex is also involved in AD, while right temporal cortex and left posterior cingulate are involved in FTD. Nuclear imaging could be a useful biomarker for revealing apathy underlying mechanisms, resulting in directed treatments. KEYPOINTS: Underlying neural networks and clinical manifestation of apathy may differ between AD and FTD. Apathy in AD is correlated with hypoperfusion in bilateral frontal areas, more prominent on the right, left anterior cingulate and right occipital cortex. Apathy in FTD is correlated with hypoperfusion in bilateral frontal areas, bilateral anterior cingulate, left posterior cingulate and right temporal cortex. Brain perfusion SPECT with automated BAs analysis and comparison with normal healthy subjects may provide significant information for apathy mechanisms in neurodegenerative disorders, affecting patients' treatment.